Caminar la ciudad (2020)
Transformation, action and effect of transforming. To transform, to change the form of something or someone. Transition, formation, transformation. Process of change from one form to another, where we accept that everything is or has a form, material or immaterial, where emptiness counts and occupies. The essence of transformation makes us intuit that there is no loss. Is destruction then anchored in opposition or parallel to transformation? Destruction makes matter lose its essence, but creates non-matter? It creates the voids that complete matter, that allow matter itself to exist. Transformation can then (re)mold the existing (is re-modeling the same thing?). One never starts from zero: Bogota already exists. It is in perpetual transformation, when the landscape changes and so do its inhabitants. How to understand the cycles: those of humans, those of materials, those of the city? Its forms change and its living changes: but what to do with this existing, to destroy it, to take advantage of it, to adapt it? Adapting the existing also implies destroying parts of the existing. How to favor the changes of living by adapting a city that already exists and already lives?